Nuclear Power Production: The Future or the Past? - Kashurnikov, Sergey; Prasolov, Valeriy; Gorbanyov, Vladimir; Rogulin, Rodion (International Journal of Energy Economics and Policy, 2020)
Over the past 20 years, the share of nuclear energy in global electricity production decreased from 17.6% to 10%. The article highlights the financial challenges of the RW repository, the synergistic combination of all investments, and the development of a forecasting model for the cost of RW storage and disposal. The control and management of cash flows between financial resources in the field of nuclear energy create new development vectors and define trends for the international nuclear industry and markets. The objective of the article is to analyze the future development of nuclear energy by applying a predictive approach in the context of the Limited Risk Distributor (LRD) business management model. The present paper analyses the trends in the global development of nuclear energy, the political background of the RW disposal, types of radioactive wastes, and their burial in Russia. The results achieved allow improving the typical LRD model for managing international nuclear enterprises by limiting the influence of commercial interests. However, a key problem of improving the efficiency of public and private investment was noted. A vague understanding of methods and forms of investment causes inefficiency and a lack of internal logic of the financing process. Keywords: LRD management business model; nuclear energy; nuclear waste; storage and disposal. JEL Classifications: O13, P28, Q4 DOI: https://doi.org/10.32479/ijeep.9765